2021
DOI: 10.21873/invivo.12508
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Advanced Breast Cancer Presentation: Possible Effect of Coronavirus Pandemic Anxiety

Abstract: Background/Aim: Corona virus infection dramatically spread worldwide during 2020 and extraordinary restrictions have been implemented in order to reduce viral transmission. These measures compelled a complete restructuring of the health system, including temporary cancer screening suspension and a significant slow-down in cancer diagnoses and treatments. Case Report: We report five cases of extremely advanced breast cancer referred to our Department amid the COVID-19 pandemic. These patients exhibited a poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Chemotherapy treatment modifications during the COVID-19 outbreak at a community cancer center in New York City. 43…”
Section: Clinical and Experimental Dermatologymentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotherapy treatment modifications during the COVID-19 outbreak at a community cancer center in New York City. 43…”
Section: Clinical and Experimental Dermatologymentioning
confidence: 99%
“…24 After the content analysis, five broad categories were identified that reflect the predominant perspectives concerning PC and breast cancer within the context of the pandemic. These included general recommendations for standard palliative treatment and symptom management, [25][26][27][28][29][30][31] the use of palliative RT, 6,[22][23][24][32][33][34][35][36][37][38][39][40][41] palliative chemotherapy, 35,38,[42][43][44][45] management of metastatic breast cancer, 22,27,[46][47][48][49][50] and teleoncology for the provision of PC 30,[51][52][53][54][55][56] The summary of the main recommendations is shown in (Table 2).…”
Section: Annals Of Surgical Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic has had a profoundly negative impact on the care of breast cancer patients, whose outcomes largely depend upon early detection and timely treatment. 1 Breast cancer patients experienced major disruptions to their care as COVID‐19 surges overwhelmed hospitals and outpatient facilities. 2 , 3 , 4 , 5 In addition, patients themselves frequently postponed or canceled scheduled visits due to fear of contracting COVID‐19 in health care settings.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 In addition, patients themselves frequently postponed or canceled scheduled visits due to fear of contracting COVID‐19 in health care settings. 1 These compounded care delays resulted in unmanaged symptoms and pathologic upstaging, 6 burdening patients with more intensive treatments, poorer outcomes, and increased care costs. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%